Recurrent Enlarging Mesenteric Desmoid Tumor following Remote Surgical Resection - Connie Hapgood; Allison DeLong (Case Reports in Radiology)
Intra-abdominal desmoid tumors are commonly associated with genetic syndromes such as familial polyposis coli. Radiological cross imaging studies such as CT and MRI are used in the preoperative work-up of such tumors. Postoperatively, CT and MRI are useful in the assessment of recurrent desmoid tumors. MRI is more accurate in tissue characterization. Where possible, surgical resection remains the standard first-line treatment. For patients where surgery is not possible, or the resection margins are not clear, other forms of treatment are possible. These include hormonal and nonhormonal options. We present a case of a recurrent sporadic intra-abdominal (mesenteric) desmoid tumor. Such an entity is rare with few cases reported in the literature. Treatment options regarding intra-abdominal desmoid tumors will be discussed.